1999
DOI: 10.1177/088307389901400704
|View full text |Cite
|
Sign up to set email alerts
|

Extrapontine Myelinolysis With Involvement of the Hippocampus in Three Children With Severe Hypernatremia

Abstract: Central pontine myelinolysis is a disorder of unknown etiology linked to overly aggressive correction of hyponatremia. In addition to the typical location of demyelination with preservation of neurons and axon cylinders in the basis pontis, similar lesions have been described in extrapontine locations. Central pontine myelinolysis and extrapontine myelinolysis usually occur together, and are identified at autopsy rather than in life because symptoms of extrapontine myelinolysis are often masked in the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 42 publications
1
60
1
13
Order By: Relevance
“…Both CPM 62,63 and EPM presentations are frequently encountered in pediatric patients, with extrapontine lesions reported to be thalamic, 64,65 in the basal ganglia, 66 and hippocampal. 67 Despite similar distributions of lesions, pediatric patients have better recovery and the associated MR imaging lesions are more reversible, 41,68 results that may be related to age-associated changes in osmotic regulatory mechanisms. It has been shown that water, electrolytes, and organic osmole (mainly taurine) content in the brain of normonatremic rats decreases with age, implying that young brains might have a greater capacity to counteract osmotic perturbations.…”
Section: Topographic Distribution Of Ods In Hypernatremiamentioning
confidence: 99%
“…Both CPM 62,63 and EPM presentations are frequently encountered in pediatric patients, with extrapontine lesions reported to be thalamic, 64,65 in the basal ganglia, 66 and hippocampal. 67 Despite similar distributions of lesions, pediatric patients have better recovery and the associated MR imaging lesions are more reversible, 41,68 results that may be related to age-associated changes in osmotic regulatory mechanisms. It has been shown that water, electrolytes, and organic osmole (mainly taurine) content in the brain of normonatremic rats decreases with age, implying that young brains might have a greater capacity to counteract osmotic perturbations.…”
Section: Topographic Distribution Of Ods In Hypernatremiamentioning
confidence: 99%
“…Demyelination in pontine or extrapontine locations does not appear exclusively in adult or alcoholic patients with hyponatremia 12 but may occur when the serum sodium level is normal 13,14 or elevated 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…As lesões pontinas podem estar associadas à mielinólise extrapontina (MEP), a qual pode acometer de maneira simétrica os pedúnculos cerebelares, núcleo caudado, putame, substância branca frontal e temporal, fórnix, cápsula externa e extrema, claustro, tálamo, núcleo subtalâmico, cápsula interna, núcleo amigdalóide, corpo geniculado lateral, camadas profundas do córtex cerebral, hipocampo e corpo caloso 3,4,[6][7][8][9] .…”
Section: Introductionunclassified
“…Alguns distúrbios parecem acarretar predisposição ao desenvolvimento dessa complicação, como insuficiência hepática, transplante hepático, cirurgia de ressecção de tumor da hipófise, queimaduras graves, insuficiência renal crônica, hemodiálise, linfoma, carcinoma, desnutrição, infecções bacterianas graves, desidratação, desequilí-brios eletrolíticos (hiponatremia, hipernatremia 7 , hiperglicemia, hipocalemia 6 , diabetes), pancreatite hemorrágica aguda e alcoolismo crônico, entre outros 4,6,7,9,12 .…”
Section: Introductionunclassified
See 1 more Smart Citation